Changes in virus transmission dynamics following the emergence of RHDV2 shed light on its competitive advantage over previously circulating variants. Issue 3 (30th March 2021) - Taggart, Patrick L.; Hall, Robyn N.; Cox, Tarnya E.; Kovaliski, John; McLeod, Steven R.; Strive, Tanja
Abstract: Rabbit haemorrhagic disease virus (RHDV) is highly pathogenic to European rabbits. Until recently, only one serotype of RHDV was known, GI.1/RHDV. RHDV2/GI.2 is a novel virus that has rapidly spread and become the dominant pathogenic calicivirus in wild rabbits worldwide. It is speculated that RHDV2 has three competitive advantages over RHDV: (a) the ability to partially overcome immunity to other variants; (b) the ability to clinically infect young rabbits; and (c) a wider host range. These differences would be expected to influence virus transmission dynamics. We used markers of recent infection (IgM/IgA antibodies) to investigate virus transmission dynamics pre and post the arrival of RHDV2. Our data set contained over 3, 900 rabbits sampled across a 7‐year period at 12 Australian sites. Following the arrival of RHDV2, seasonal peaks in IgM and IgA seropositivity shifted forward one season, from winter to autumn and spring to winter, respectively. Contrary to predictions, we found only weak effects of rabbit age, seropositivity to non‐pathogenic calicivirus RCV‐A1 and population abundance on IgM/IgA seropositivity. Our results demonstrate that RHDV2 enters rabbit populations shortly after the commencement of annual breeding cycles. Upon entering, the population RHDV2 undergoes extensive replication in young rabbits, causing clinical disease, high virus shedding, mortality and the creation of virus‐laden carcasses. This results in high virus contamination in the environment, furthering the transmission of RHDV2 and initiating outbreaks, whilst simultaneously removing the susceptible cohort required for the effective transmission of RHDV. Although RHDV may enter the population at the same time point, it is sub‐clinical in young rabbits, causing minimal virus shedding and low environmental contamination. Our results demonstrate a major shift in epidemiological patterns in virus transmission, providing the first evidence that RHDV2's ability to clinically infect young rabbits is a key competitive advantage in the field.